Academic integrity and academic charisma of the scientist: values of openness and trust - Шашкова, Л.; Крилова, С. (Київський національний університет імені Тараса Шевченка, 2024)
The features of the connection between academic integrity and academic charisma of a scientist are considered. The question is topical in modern society because, on the one hand, scientific and educational institutions, especially universities, are increasingly competing in the scientific field. On the other hand, scientific achievements require social approval and social acceptability. The ethos of science is comprehended, including its system of norms and values that regulate the activities of the scientific community, unite it into a whole, and establish connections with society. A high degree of trust in society towards the profession of a scientist and its reasons are demonstrated. It is revealed that the requirement to adhere to the values of scientific research – openness, objectivity, honesty, and solidarity – is possible only with the responsible attitude of scientists to defining criteria for proper research behavior and adequate response to violations of virtues. The principles of academic integrity are considered in this understanding. At the same time, it is shown that science is a personal activity that requires concentration and individual self-immersion. Academic charisma is defined as the scientist's ability to make personal discoveries arising in a co-creative communicative space that includes the past, present, and future. The presence of academic charismatics in the educational and scientific space enlivens academic integrity, overcoming its formal and even self-repressive nature. It is demonstrated that the path of a true scientist lies in moving from academic integrity, where one studies the previous tradition and honestly finds one's place among existing directions, to academic charisma, where there is an opportunity to create one's own direction and school. The academic charisma of a teacher, their immersion in the process of their own scientific creativity, inspires their students and followers to their own creativity. As a result, academic integrity becomes not something external and repressive but an internal core of a young scientist resonating with the need and ability to create in scientific activities.

Розглянуто особливості зв'язку академічної доброчесності й академічної харизми вченого. Питання в сучасному суспільстві актуалізовано тим, що, з одного боку, наукові й освітні установи, передусім університети, усе інтенсивніше конкурують між собою у науковій сфері. А з іншого боку, наукові досягнення потребують соціального схвалення і соціальної прийнятності. Розглянуто етос науки, його система норм і цінностей, яка регулює діяльність наукової спільноти, об'єднує у цілісність, встановлює зв'язки із суспільством. Показано високий ступінь довіри в суспільстві до професії вченого та його причини. Розкрито, що вимога дотримання цінностей наукових досліджень – відкритості, об'єктивності, чесності, солідарності – здійснима лише за умови відповідального ставлення учених до визначення критеріїв належної дослідницької поведінки та адекватного реагування на порушення чеснот. У такому розумінні розглянуто принципи академічної доброчесності. Водночас показано, що наука – це діяльність особиста, яка потребує зосередженості й індивідуального самозаглиблення. Академічну харизму визначено як здатність ученого до особистісних винаходів, які виникають у співтворчому комунікативному просторі, що включає у себе минуле, сучасне і майбутнє. Наявність академічних харизматиків у освітньому й науковому просторі оживлює академічну доброчесність, долає її формальний і навіть саморепресивний характер. Показано, що шлях справжнього вченого – у русі від академічної доброчесності, коли він вивчає попередню традицію і чесно знаходить своє місце серед наявних напрямів, до академічної харизми, коли в нього з'являється можливість створити власний напрям і школу. Академічна харизма викладача, його зануреність у вир власної наукової творчості ініціює його учнів і послідовників на власну творчість. У результаті академічна доброчесність стає не чимось зовнішнім і репресивним, а внутрішнім стрижнем молодого вченого, який резонує з потребою і здатністю творити в науковій діяльності.
Академічна доброчесність і академічна харизма вченого: цінності відкритості й довіри
Keywords: science; scientist; academic integrity; academic charisma; trust; ethos of science; scientific creativity; академічна доброчесність; академічна харизма; наука; учений; довіра; етос науки; наукова творчість